Application of PowerPoint Media in Think Pair Share (TPS) Cooperative Learning to Increase Students' Learning Activity and Independence - Fathiyah, Intan Azka; Sahlan, Moh.; Usriyah, Lailatul; Mundir, Mundir (Journal of Science and Education (JSE), 2025)
This study examines how PowerPoint media can increase student activeness and independence in Think Pair Share (TPS). This report uses a case study from a junior high school with several pupils as subjects. PowerPoint is utilized to show learning materials interactively and interestingly, and the TPS learning paradigm encourages student involvement. Data is collected by observation, interviews, and documentation analysis and examined descriptively qualitatively. The study found that PowerPoint media in TPS cooperative learning increases student involvement in group discussions and partner idea sharing. Because it encourages students to actively seek information and share opinions, this media also boosts learning freedom. The TPS learning paradigm using PowerPoint media creates a more dynamic learning environment and improves classroom learning, according to this study. This study examines how PowerPoint media can improve students' active and independent learning in cooperative Think Pair Share (TPS) learning. This report uses a case study from a junior high school with several pupils as subjects. Power-Point media is used to make learning materials interactive and exciting, and the TPS learning approach encourages student involvement. Data was collected by observation, interviews, and documentation analysis and examined qualitatively. The study found that PowerPoint media in TPS cooperative learning increases student activity in group discussions and when sharing opinions with partners. Because this media encourages students to actively seek information and share opinions, it also boosts learning freedom. The TPS learning paradigm using PowerPoint media creates a more dynamic learning environment and improves classroom learning, according to this study